Physical Fitness of Basketball Players: The Importance of Endurance, Speed and Strength - Ashurova Ibotkhon Ilhomjon qizi (Scientific Trends, 2025)
Basketball is a high-intensity sport in which the physical fitness of players is one of the keys to success. This article comprehensively studies the importance of endurance, speed and strength indicators in basketball players. Endurance helps to maintain high performance during a long game, while speed plays an important role in gaining an advantage over the opponent and performing movements optimally. The strength factor ensures the athlete's stability in contact fights, jumps and defensive movements. The article covers training systems and recommendations for basketball players aimed at developing these three aspects. The study is based on sports physiology and practical training methodologies and is aimed at maximizing the physical fitness of basketball players.
Keywords: Basketball, physical fitness, endurance, speed, strength, sports training, competition efficiency.